1995
DOI: 10.1111/j.1600-0528.1995.tb00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral health data from self‐administered questionnaire and clinical examination

Abstract: In order to assess the validity of self-reported oral health data 319 subjects randomly selected from the respondents to an oral health survey were examined clinically. The level of agreement between the two methods of examination was estimated by the kappa statistic. Substantial agreement (kappa = 0.65) was found between the reported and observed number of remaining teeth and the difference between underreporting and overreporting was small. The results indicate that valid data for planning purposes and for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 5 publications
8
80
0
2
Order By: Relevance
“…However, a number of studies have examined the validity of self-reported dentate status, denture wearing or number of remaining teeth compared with a 'gold standard' assessment by clinicians and found high levels of agreement. 22,23 We believe that these relatively minor methodological differences would have only a small impact on prevalence estimates and would be ver y unlikely to account for the large differences observed over time, and among age groups, the sexes, and States/Ter ritories.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, a number of studies have examined the validity of self-reported dentate status, denture wearing or number of remaining teeth compared with a 'gold standard' assessment by clinicians and found high levels of agreement. 22,23 We believe that these relatively minor methodological differences would have only a small impact on prevalence estimates and would be ver y unlikely to account for the large differences observed over time, and among age groups, the sexes, and States/Ter ritories.…”
Section: Discussionmentioning
confidence: 96%
“…13 The NDTIS is a cross-sectional telephone interview survey of Australian residents aged five years and over that has been conducted by the Dental Statistics and Research Unit of the Australian Institute of Health and Welfare in 1994, 1995, 1996. In 1994, households were sampled by selecting telephone numbers listed in the Electronic White Pages telephone directory for all States and Ter ritories.…”
Section: Methods Datasetsmentioning
confidence: 99%
“…The validity of self-assessed remaining teeth has been evaluated using telephone interview and mail survey methods and was found to closely approximate clinical assessments. [24][25][26][27] Rates of participation (56.6%) and response (64.6%) were not high enough to justify a claim that findings reflect the total population and not just those in the sample. To help minimise the impact of non-response we used recommended methods of survey design and weighted the data to reflect the age and sex distributions in each sampling stratum and adjusted for differences in the probabilities of selection.…”
Section: Discussionmentioning
confidence: 97%
“…Axelsson and Helgadóttir reported that the kappa statistic for agreement between the self-reported number of remaining teeth and the number found at a clinical examination in the 18-y group, 35-to-44-y group, and the group aged 65 y or older were 0.56, 0.60, and 0.63, respectively ( 21 ). Persons are more knowledgeable about tooth loss than about signs and symptoms of disturbances of oral health, such as toothache, sore or swollen gums, and sensitivity of teeth to cold or heat ( 22 ).…”
Section: Discussionmentioning
confidence: 99%